2004
DOI: 10.1179/136217104225021698
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of simulated heat affected zone areas in HSLA structural steel

Abstract: The fracture toughness of some areas in the multi-pass heat affected zone (HAZ) of a high strength low alloy (HSLA) structural steel was analysed in a straightforward way using precracked, cylindrical specimens tested on a conventional tensile machine. The specimens were made from samples with a simulated HAZ microstructure; however, the size of the samples was restricted by the limitations of the Gleeble machine. The brittleness of the samples was an indication of the detrimental effect of welding on their to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Some of them, like inclusions, are intrinsic while others happening at different microstructural scales relate to processing conditions (Gutiérrez, 2014). Figure 4 (Gliha et al, 2004) shows schematically the changes of microstructure that occur in a multiple-pass weld. The zone affected by heat, whose microstructure is thickened by the first cycle, changes to different microstructures according to the thermal sequence of the subsequent passes.…”
Section: Background Of the Charpy Testmentioning
confidence: 99%
“…Some of them, like inclusions, are intrinsic while others happening at different microstructural scales relate to processing conditions (Gutiérrez, 2014). Figure 4 (Gliha et al, 2004) shows schematically the changes of microstructure that occur in a multiple-pass weld. The zone affected by heat, whose microstructure is thickened by the first cycle, changes to different microstructures according to the thermal sequence of the subsequent passes.…”
Section: Background Of the Charpy Testmentioning
confidence: 99%
“…In a case of the welding joint, the deformation process which take place during the first stage are more dangerous since it is not uniformed and is under the assumption which represents by its composition 'welding seam Á zone of the thermal influence' (WSÁZthI) and necessarily contains the inhomogeneities of the structure as different admixtures and defects (Gliha et al 2004(Gliha et al , 2009(Gliha et al , 2011. This causes the concentration of tensions in the zone of the welding joint and additional risks of the breakage or failure takes place in the stages of the building or exploitation.…”
Section: Fatigue Damage Of Welded Jointsmentioning
confidence: 99%
“…Curiel-Reyna et al (2006) have recently shown the strength and toughness of the HSLA microalloyed steels can be damaged by the thermal cycles during welding, causing fragility in the HAZ. Gliha et al (2004) have reported for single pass welding, the lowest toughness is expected in the coarse grained heat affected zone (CGHAZ), which is part of the HAZ near the fusion line. Moeinifar et al (2010) have recently reported welding processes with high heat input, such as tandem submerged arc welding (TSAW), cause larger prior-austenite grain sizes in the CGHAZ.…”
Section: Introductionmentioning
confidence: 97%